Analisis Tingkat Kebahagiaan Pensiunan: Studi Kasus IFLS 2007 dan 2014 - Fadhilah, Hana; Indrawati, Dini (PT Literasi Nusantara Publisher, 2023)
The population within the retirement age range in Indonesia, which falls into the pre-elderly to old-elderly group, has increased over the last 50 years. This indicates that Indonesia has entered an aging population phase. While retirement can have positive impacts that increase happiness, it can also reduce one's level of happiness. Thus, the objective of this study is to examine the degree of happiness in Indonesian retirees and determine the most influential factors on their happiness. Data from IFLS 4 in 2007 and IFLS 5 in 2014 will be used with logistic regression as the method. The findings of this research indicate that retirees have higher level of happiness compared to individuals who are not retirees.